Analysis of power frequency EMF under mobile phone base station - 399376 Brunson Army (Skudai : Universiti Teknologi Malaysia, 2006)
Project paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006